AFTER-CURRENTS, AFTER-POTENTIALS, EXCITABILITY, AND VENTRAL ROOT ELECTROTONUS IN SPINAL MOTONEURONS - Lloyd, David P. C. (The Rockefeller University Press, 1951)
The spinal cord constitutes a volume conductor. Potential changes are recorded therefrom only as current flows. During the period of the after-potentials current flows in significant density only if the after-polarization differs at different points of the active neurons. Thus one does not record after-potentials in volume; one may record after-currents which are defined as the resultants of differences in after-potentials. Measurable excitability change during the period of the after-potentials, in the event no current flows, might be regarded as approximating the change of intrinsic polarization status at the region tested. In the presence of after-current flow excitability change would approximate the sum of intrinsic change and extrinsic change due to current flow. In giving rise by differences to current flow after-potentials come to act as agents, and events in one part of a neuron help to determine excitability in other parts. Since the intramedullary after-current flow is not the after-potential of the soma, it follows that ventral root electrotonus which results from axonal after-current flow cannot be considered the counterpart of somatic after-potential. Following conduction of an antidromic volley after-current flows between somata and axons. According to the signs of the recorded potential changes, after-current flow initially, and for approximately 45 msec., is in the direction from somata to axons. Thereafter, and for approximately another 75 msec., the direction of flow is reversed. During the period of after-current flow following antidromic conduction the excitability of neighboring motoneurons is altered in a manner that reproduces the phases of after-current flow. The initial phase, depression, was first described by Renshaw. The after-potentials of ventral root fibers have been studied. In a single action and in usual form, they consist of a negative after-potential of considerable magnitude and of some 35 msec. duration, and a positive after-potential detectable for approximately 120 msec. Variants and the influence of temperature change are described. The recovery cycle of ventral root axons in general compares with the after-potential cycle. Recovery of intramedullary motor axons differs from that of their extramedullary projections as ventral root fibers in a manner that is accountable to intramedullary flow of after-current. Since the intrinsic recovery process of the motoneuron somata cannot be measured in the presence of current flow it must be estimated by correcting the observed recovery for the influence of known current flows. When this is done the resultant in simplest form provides for intrinsic somatic recovery from refractoriness through a single phase of subnormality lasting some 60 msec. Conditions for the relatively undistorted recording of antidromic ventral root electrotonus are described. They include provisions that the proximal ventral root electrode must be within 12 mm. of the root-cord junction and that the distal electrode must be located in excess of 30 mm. from the distal severed end of the ventral root. Antidromic ventral root electrotonus is a counterpart of the current flows in the intramedullary stretch of the axons. Initially, during the phase of metadromal postivity of the intramedullary axons, electrotonus is negative. During the period of deflections Sp-An, that signify after-current flow into the axons, electrotonus is positive. Finally during the period of deflections Sn-Ap, that signify after-current flow outwards through the intramedullary axon membranes, electrotonus is negative. Electrotonic showing is not of sufficient magnitude to make the time course of ventral root electrotonus palpably different from that of the generating intramedullary currents.